Analisis dan Upaya Preventif Risiko Tingkat Kebisingan Pekerjaan MEP (Mechanical, Electrical, Plumbing) Konstruksi Rumah Susun di Ibu Kota Negara - Moch. Andy Wibisono; Muhammad Abdus Salam Jawwad (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Construction work is one of the jobs that has various high risks for workers and people who are around it. These risks come from various sources, one of which is noise from various equipment and ongoing activities. One of the jobs that cause high noise in construction work is MEP (Mechanical Electrical Plumbing) work. Based on Permenaker Number 13 Year 2011, the Threshold Value (NAB) for noise that can be accepted by workers is 85 dBA for 8 hours a day. Based on the measurement of the construction of the flats, the MEP work in the form of Beam Separator Elevator Installation, Pipe Fabrication, Electrical Wiring Lighting Installation, as well as Welding and Grinding of Iron Pipe causes noise above the NAB. The highest noise comes from pipe fabrication in the form of iron pipe cutting activities using large grinding tools and bevel machines that produce noise of 107 dBA. From the Daily Noise Dose (DND) calculation, the noise generated from MEP work has a dangerous risk level for workers' hearing. Risk control efforts that can be done are preventive actions based on the K3 hierarchy in the form of administrative controls such as changing working hours or shifts and conducting safety talks before work is carried out. In addition, another preventive measure is the use of PPE such as ear plugs. Based on the calculation of the noise reduction level, the use of ear plugs has not reduced the noise level to reach the NAB, so it is recommended that workers in pipe fabrication work use ear muffs to reduce noise exposure.